2021
DOI: 10.1016/j.ejrad.2020.109448
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence applications for oncological positron emission tomography imaging

Abstract: Positron emission tomography (PET), a functional and dynamic molecular imaging technique, is generally used to reveal tumors' biological behavior. Radiomics allows a high-throughput extraction of multiple features from images with artificial intelligence (AI) approaches and develops rapidly worldwide. Quantitative and objective features of medical images have been explored to recognize reliable biomarkers, with the development of PET radiomics. This paper will review the current clinical exploration of PET-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 98 publications
0
6
0
1
Order By: Relevance
“…This high-throughput strategy to mine quantitative data from medical images searching for novel biomarkers and to generate decision-support models is deemed a feasible approach to overcome the limitations of conventional image interpretation, particularly in oncology [3][4][5]. The potential applications of radiomics are seemingly endless across all imaging modalities, and according to a survey study, the future physicians are confident that advanced computer-aided image analyses will revolutionize radiology for the best [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This high-throughput strategy to mine quantitative data from medical images searching for novel biomarkers and to generate decision-support models is deemed a feasible approach to overcome the limitations of conventional image interpretation, particularly in oncology [3][4][5]. The potential applications of radiomics are seemingly endless across all imaging modalities, and according to a survey study, the future physicians are confident that advanced computer-aided image analyses will revolutionize radiology for the best [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, research on PET-based quantitative evaluation of cancer using artificial intelligence (AI) and deep learning has been actively conducted [ 27 , 28 ]. Multiple studies suggested AI could enhance the characterization and quantification of tumors and predict treatment response and risk stratification of recurrence [ 29 ]. Although it is still challenging to apply AI-based procedures routinely in clinical practice, it is expected that experiences and data will be gradually accumulated, and more effective clinical application of FDG-PET/CT on lymphoma will be achieved.…”
Section: Current Role Of Fdg-pet/ct In the Management Of Lymphoma And...mentioning
confidence: 99%
“…For the interpretation of images, studies on an AI-based triage system for identifying artifacts have been published recently[ 15 ]. In the near future, similar systems will be able to detect directly using raw data, such as sinograms, and issue alarms throughout the scanning process, even before reconstruction, so that technicians can adjust or prolong the scheduled scan procedure to accommodate an unexpected discovery[ 16 ].…”
Section: Applicationsmentioning
confidence: 99%